Duties and Authorities of the Sub-district Head as Temporary PPAT in Making Deeds Concerning Land (Study in Batang Regency) - Pratama, Aditya Nur (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Duties and authorities of the sub-district head as a temporary PPAT in making land deeds (study in Batang Regency) Land Deed Making Officers (PPAT) Notaries in Batang Regency have not yet reached sub-districts far from the city, this is a problem considering the vastness and spread of these areas. Therefore, in order to achieve equal legal certainty in the agrarian sector, especially land registration, once again the role of the sub-district head is still very much needed. The following problems arise: 1) Why are there no Sub-district Heads in Batang Regency who are Temporary PPATs?, 2) What is the role of the Sub-district Head who is appointed as Temporary PPAT in the Land Registration process in Batang Regency, Central Java?, 3) What are the obstacles faced by the Sub-district Head as a Temporary Land Deed Making Officer in the Land Registration Process in Batang Regency, Central Java? The objectives to be achieved from this study are: 1) To find out the reasons or factors that cause all Sub-district Heads in the Batang Regency, Central Java, not to become Temporary PPATs. 2) To find out what the roles of the Sub-district Head as a Temporary PPAT official are in the Land Registration Process in Batang Regency, Central Java. 2) To find out and examine the obstacles faced by the Sub-district Head in his role as a Temporary PPAT official in the Land Registration process in Batang Regency, Central Java. The results of the research and discussion on the implementation can be concluded: 1) The implementation of the duties and authority of the sub-district head as a Temporary PPAT in making land deeds in Batang Regency is carried out in accordance with the provisions of applicable laws and regulations, 2) Several obstacles faced by the Sub-district Head as a Temporary PPAT related to the implementation of duties and authority in making land deeds, 3) Efforts made by the Sub-district Head as a Temporary PPAT in overcoming obstacles faced during the implementation of duties and authority in making land deeds.